Clinical Usefulness of Assessment of Ankle–Brachial Index and Carotid Stenosis in Type 2 Diabetic Population—Three-Year Cohort Follow-Up of Mortality. (January 2013) - Bosevski, Marijan; Peovska, Irena
We evaluated the clinical usefulness of assessing the ankle–brachial index (ABI) and carotid stenosis (CS) in a type 2 diabetic population. Patients with type 2 diabetes and coronary artery disease (n = 265) were enrolled in a prospective 3-year cohort study. The cardiovascular mortality rate was 8.7% (23 of 265) during the 36-month study and the all-cause mortality rate was 9.5% (25 of 265). Multivariate logistic regression analysis revealed that age (odds ratio [OR] 2.09), hypertension (OR 7.99), obesity (OR 4.86), internal CS (OR 262.17), and Gensini score (OR 1.15) were independent predictors of cardiovascular mortality. Mean ABI value (OR 0.15) was the only predictor of all-cause mortality in this population. The ABI and carotid artery ultrasound have independent prognostic value in a type 2 diabetic population.